1994
DOI: 10.1007/bf02444071
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activity and evoked potentials in the caudal trigeminal nucleus, ventrobasal thalamus, and cerebral cortex of rats with neuropathic trigeminal neuralgia

Abstract: Incomplete compression of the infraorbital nerve in rats leads to spontaneous netlronal activity in the form of bursts in the caudal trigeminal nucleus and to epileptiform activity in the ventrobasal thalamus and cerebral cortex. From the latter, afterdischarges are also recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, if the bioelectrical activity recorded in EEG originates from two or more generators, the three-dimensional model results in only some average distribution of electric activity sources, which does not clearly show the locations of the corresponding generators [1]. According to the theory of generator and system mechanisms [4], the generator corresponding to trigeminal neuralgia and located in the brainstem nuclei of the trigeminal system, can induce formation of secondary pathological generators at higher cerebral levels. Therefore, when generators of different levels are working simultaneously, it is not always possible to localize the pathological activity sources.…”
Section: Bulletin O F Experimental Biology and Medicine N ~ -9 1997mentioning
confidence: 98%
See 1 more Smart Citation
“…However, if the bioelectrical activity recorded in EEG originates from two or more generators, the three-dimensional model results in only some average distribution of electric activity sources, which does not clearly show the locations of the corresponding generators [1]. According to the theory of generator and system mechanisms [4], the generator corresponding to trigeminal neuralgia and located in the brainstem nuclei of the trigeminal system, can induce formation of secondary pathological generators at higher cerebral levels. Therefore, when generators of different levels are working simultaneously, it is not always possible to localize the pathological activity sources.…”
Section: Bulletin O F Experimental Biology and Medicine N ~ -9 1997mentioning
confidence: 98%
“…Irrespective of the nature of the initiating factor of the paroxysmal trigeminal neuralgia syndrome, the pathological basis of its realization is the pathoalgetic system formed under the action of pathological superactive neumgenerator in the trigeminal nerve system [4]. Pathological discharges produced by this generator and conveyed via specific and nonspecific conducting pathways modify the spontaneous and evoked bioelectrical cerebral activity [5,6].…”
mentioning
confidence: 99%
“…Torusseau first identified TN epileptic symptoms in 1853 with some studies reporting abnormal discharge phenomena in the ventral thalamus and cerebral cortex in the TN model 72 Many studies have reported that SCs can relieve neuropathic pain 9,14,15 by remyelinating injured nerves. In addition, we have previously reported that SC transplantation can reduce neuropathic pain caused by nerve injury 75 .We micro-encapsulated SCs in alginic acid and transplanted microencapsulated SCs and non-microencapsulated SCs into the region surrounding the injured sciatic found that the myelin sheaths in the injury areas healed better than those without SCs.…”
Section: Tn Treatmentmentioning
confidence: 99%
“…31,71 Before 1871, Torusseau first proposed the epileptiform pain symptoms of TN, and some scholars observed abnormal discharge phenomena in the ventral thalamus and cerebral cortex in the TN model. 72 This suggests that abnormal discharge of the ventral thalamus and cerebral cortex might cause TN. Moreover, chronic electrical stimulation of the central sulcus motor cortex in patients with TN was reported to have an effective response rate of 40%100%, 73 which suggests an association between abnormal electrical activity in the brain and TN.…”
Section: Tn Treatmentmentioning
confidence: 99%